Anisotropic characteristics of jointed rock mass: A case study at Shirengou iron ore mine in China. (April 2015) - Yang, Tianhong; Wang, Peitao; Xu, Tao; Yu, Qinglei; Zhang, Penghai; Shi, Wenhao; Hu, Gaojian
Graphical abstract: Highlights: An anisotropic model is introduced and applied in Shirengou iron mine. We examine the numerical damage zone comparing with the microseismic data. The stress and damage zones are influenced by the anisotropy of rock mass. The influence of joints cannot be neglected in stability analysis of rock mass. Abstract: Rock mass is characterized by the existence of distributed joints whose properties and geometry strongly affect the mechanical behavior of jointed rock masses. A finite element model considering the anisotropic characteristics of fractured rock mass was proposed which could deal with a wide variety of joint distribution in rock mass and then applied in Shirengou iron ore mine in Tangshan, China. First, the scale effects and anisotropy were investigated by using multi-scale discrete fracture network models under uniaxial compression tests. Then, the principal direction of elasticity was found and used in the constitutive law of the equivalent continuum model. Finally, the deformation and failure behavior were studied and verified through site-specific microseismic data. It is found that the stress and damage zone are influenced by joint orientation. This proposed model can efficiently study the effects of rock joints on rock mass behavior and thus contribute to a more reasonable explanation on the dominant effect of the joint sets on deformation and failure of rock mass.